Health Care Resource Utilization of Late Premature Versus Term Infants With Bronchiolitis. (July 2020) - Greenberg, David; Dagan, Ron; Shany, Eilon; Ben-Shimol, Shalom; Givon-Lavi, Noga
It is controversial whether it is cost-beneficial for late preterm infants to receive respiratory syncytial virus prophylaxis. This study compares community and hospital health care resource utilization (HCRU) of late premature infants (33-36 weeks gestational age) with term infants (>36 weeks gestational age) hospitalized with bronchiolitis. This was a retrospective, population-based, observational study spanning a 9-year period (2004-2012). HCRU data were obtained from the Health Maintenance Organization "Clalit" and included duration of hospitalization, physician visits, laboratory tests, and treatments. Compared with term infants, late preterm infants had significantly longer duration of hospitalization and higher admission rates to pediatric intensive care unit. They also had higher rates of mean outpatients clinic visits, total outpatient clinic and specialist visits, blood chemistry, and virology testing. HCRU of term infants with bronchiolitis was also substantial, indicating that they also can greatly benefit from respiratory syncytial virus prophylaxis. These findings can guide stakeholders in decisions concerning the prevention of bronchiolitis and will be useful in performing further cost-benefit analysis.